Image/thinking. (17th July 2012) - Becker, Claudia
This article re-examines Vilém Flusser's philosophy of photography and its relation to what I will name the philosophical question of 'image-thinking'. It places his work on photography in the context of the much discussed 'pictorial' and 'iconic' turns in the study of visual culture and, through this, aims to reveal the depth of Flusser's approach to understanding media culture and to argue for the significance and continuing relevance of his philosophy of photography.